Petro : ¿el caudillo de los indignados? : palabras de Gustavo Petro Urrego en la Plaza de Bolívar de Bogotá - Petro, Gustavo (Editorial La Oveja Negra Ltda., 2014)
Consists primarily of addresses delivered by Petro as Alcalde Mayor of Bogotá between December 9, 2013, and January 13, 2014, in part regarding an attempt by the Procuraduría General of Colombia to remove him from office.